Teresa my love : an imagined life of the saint of Avila - Kristeva, Julia, 1941-; Fox, Lorna Scott (New York : Columbia University Press, 2015)
Mixing fiction, history, psychoanalysis, and personal fantasy, Teresa, My Love turns a past world into a modern marvel, following Sylvia Leclercq, a French psychoanalyst, academic, and incurable insomniac, as she falls for the sixteenth-century Saint Teresa of Avila and becomes consumed with charting her life. Traveling to Spain, Leclercq, Julia Kristeva's probing alter ego, visits the sites and embodiments of the famous mystic and awakens to her own desire for faith, connection, and rebellion. One of Kristeva's most passionate and transporting works, Teresa, My Love interchanges biography, autobiography, analysis, dramatic dialogue, musical scores, and images of paintings and sculpture to engage the reader in Leclercq's--and Kristeva's--journey. Born in 1515, Teresa of Avila outwitted the Spanish Inquisition and was a key reformer of the Carmelite Order. Her experience of ecstasy, which she intimately described in her writings, released her from her body and led to a complete realization of her consciousness, a state Kristeva explores in relation to present-day political failures, religious fundamentalism, and cultural malaise. Incorporating notes from her own psychoanalytic practice, as well as literary and philosophical references, Kristeva builds a fascinating dual diagnosis of contemporary society and the individual psyche while sharing unprecedented insights into her own character.
Part 1: The Nothingness of All Things -- 1. Present by Default -- 2. Mystical Seduction -- 3. Dreaming, Music, Ocean -- 4. Homo Viator -- Part 2: -- Understanding Through Fiction -- 5. Prayer, Writing, Politics -- 6. How to Write Sensible Experience, or, of Water as the Fiction of Touch -- 7. The Imaginary of an Unfindable Sense Curled Into a God Findable in Me -- Part 3: -- The Wanderer -- 8. Everything So Constrained Me -- 9. Her Lovesickness -- Part 4: Extreme Letters, Extremes of Being -- 11. Bombs and Ramparts -- 12. "Cristo como hombre" -- 13. Image, Vision, and Rapture -- 14. "The soul isn't in possession of its senses, but it rejoices" -- 15. A Clinical Lucidity -- 16. The Minx and the Sage -- 17. Better to Hide . . .? -- 18. ". . . Or 'to do what lies within my power' "? -- 19. From Hell to Foundation -- Part 5: -- From Ecstasy to Action -- 20. The Great Tide -- 21. Saint Joseph, the Virgin Mary, and His Majesty -- 22. The Maternal Vocation -- 23. Constituting Time -- 24. Tutti a cavallo -- Part 6: Foundation-Persecution -- 25. The Mystic and the Jester -- 26. A Father Is Beaten to Death -- 27. A Runaway Girl -- 28. "Give me trials, Lord; give me persecutions" -- 29. "With the ears of the soul" -- Part 7: -- Dialogues from Beyond the Grave -- 30. Act I. Her Women -- 31. Act II. Her Eliseus -- 32. Act III: Her "Little Seneca" -- 33. Act IV. The Analyst's Farewell -- Part 8: -- Postscript -- 34. Letter to Denis Diderot on the Infinitesimal Subversion of a Nun.
Print version record.
Includes bibliographical references.
English.
Keywords: Teresa, -- of Avila, Saint, -- 1515-1582.; Teresa, -- of Avila, Saint, -- 1515-1582.; Christian saints -- Spain -- Avila -- Biography; RELIGION -- Christianity -- Catholic; RELIGION -- Christian Life -- Women's Issues; Christian saints; Spain -- Avila; Electronic books; Electronic books; Biographical fiction; Biographies; Biographical fiction